Omnidirectional and effective salt-rejecting absorber with rationally designed nanoarchitecture for efficient and durable solar vapour generation. Issue 45 (5th November 2018) - Song, Xiaoying; Song, Hucheng; Xu, Ning; Yang, Huafeng; Zhou, Lin; Yu, Linwei; Zhu, Jia; Xu, Jun; Chen, Kunji
Abstract : Harvesting solar energy as heat has shown fascinating applications for the purification of polluted or saline water to address the water scarcity issue globally. Abstract : Harvesting solar energy as heat has shown fascinating applications for the purification of polluted or saline water to address the water scarcity issue globally. One of the current challenges is to realize highly efficient solar absorbers with simultaneous efficient omnidirectional light harvesting, salt-resistance and water extraction capability. In the present study, inspired by the natural lotus leaf, we propose a self-floating silicon–copper membrane consisting of hierarchical nanoscale hybrids with effective salt-resistant characteristics. We demonstrate its efficient absorbance (>93%) in a wide spectral range (200–2500 nm) and omnidirectional character (0° to 80°). We obtained a salt-water evaporation efficiency as high as 86% under one sun irradiation. The front surface of the membrane was free of salt accumulation in salt-water even after long-term operation and complete evaporation of water. More interestingly, a significant performance improvement of ∼7.8% was achieved even after an ultra-long durability test in saltwater up to 310 days, which is attributed to the formation of a salt-induced robust super-hydrophilic interface layer on the water-pumping structure, thus enabling more efficient evaporation. The present hierarchical nanostructure design offers highly efficient solar photo-thermal conversion in wide angles and an excellent salt-rejecting technique, which can be easily recycled for highly efficient and stable solar vapour generation.